Transformasi Ekonomi dan Kewirausahaan di Desa Blimbingsari - I Wayan Ruspendi Junaedi (BISMA (Bisnis dan Manajemen), 2018)
In the development of business and the need for a process in which development is a series of conscious effort made towards a better state than before. Development is a multidimensional process of socioeconomic change.. This confirms that economic development is not a purely economic process, but rather a manifestation of the transformation or social change and cultural. Therefore, any process of economic development always involves a multidimensional factor in it. The transformation that occurred in Blimbingsari covering economic, social and cultural, among others, involve changes in the structure, initiator agent of change, towards more advanced (progress). From the description above, the authors raised three issues research, as follows: 1). What characteristic (unique) Blimbingsari Village? 2). Types of Entrepreneurial what is in the village Blimbingsari? 3). What is the role of entrepreneurship in rural Blimbingsari? The three issue of the study, the authors raised three research objectives, namely: 1). To explain the characteristic (unique) Village Blimbingsari. 2). To find out, the types of Entrepreneurial what is in the village Blimbingsari. 3). To explain the role of entrepreneurship in the village Blimbingsari. The research methodology used in this study is a qualitative research with in-depth interviews, triangulation data and oral history. The village has happened Blimbingsari economic change (economic transformation), one of which is caused by the entrepreneurial. The types of entrepreneurship that exist in Blimbingsari such as poultry, cattle farmers, pig farmers, ranchers catfish, coconut fruit seller, the seller of chocolate, grocer, refill water seller, the owner of the fields, forests sengon, food stalls and the owner of the guest house/villa. There are also other entrepreneurs as employers coconut sugar makers who become entrepreneurs in the village Blimbingsari. It becomes a matter of interest to the author, in view of the development of entrepreneurship in villages Blimbingsari. The role of entrepreneurship in villages Blimbingsari which is to reduce unemployment and through their efforts, they can survive and even be able to finance their children for further studies. They were able to improve their living standards from "nothing into something". The author's suggestion is, there may be other factors that affect the economic transformation of this village is that the author has not been through. So that other researchers can continued.